Efficacy and safety of liraglutide versus sitagliptin, both in combination with metformin, in Chinese patients with type 2 diabetes: a 26‐week, open‐label, randomized, active comparator clinical trial. Issue 8 (20th May 2016) - Zang, L.; Liu, Y.; Geng, J.; Luo, Y.; Bian, F.; Lv, X.; Yang, J.; Liu, J.; Peng, Y.; Li, Y.; Sun, Y.; Bosch‐Traberg, H.; et al.
Abstract : Aims: To compare the efficacy and safety of liraglutide versus sitagliptin as add‐on to metformin after 26 weeks of treatment in Chinese patients with type 2 diabetes mellitus (T2DM). Methods: This 26‐week open‐label, active comparator trial (NCT02008682) randomized patients (aged 18–80 years) with T2DM inadequately controlled with metformin [glycated haemoglobin (HbA1c) 7.0–10.0% (53–86 mmol/mol)] 1 : 1 to once‐daily subcutaneously administered liraglutide 1.8 mg (n = 184) or once‐daily oral sitagliptin 100 mg (n = 184), both as add‐on to metformin. The primary endpoint was change in HbA1c from baseline to week 26. Results: Liraglutide was superior to sitagliptin in reducing HbA1c from baseline [8.1% (65 mmol/mol)] to 26 weeks, as evidenced by estimated mean HbA1c change of −1.65% (−18.07 mmol/mol) versus −0.98% (−10.72 mmol/mol), respectively [estimated treatment difference for liraglutide vs sitagliptin of −0.67% (95% CI −0.86, −0.48) or −7.35 mmol/mol (95% CI −9.43; −5.26); p < 0.0001]. More patients receiving liraglutide (76.5%) than sitagliptin (52.6%) achieved the HbA1c target of <7.0% (53 mmol/mol) at week 26 [odds ratio 3.65 (95% CI 2.18, 6.12); p < 0.0001]. Reductions in fasting plasma glucose, 7‐point self‐measured plasma glucose and body weight were greater with liraglutide than with sitagliptin (p < 0.0001 for all). More patients experienced nausea (14.8% vs 0.5%), diarrhoea (8.2% vs 2.2%) and decreased appetite (10.9% vs 0.5%) with liraglutide than sitagliptin. Two hypoglycaemic episodes were confirmed for liraglutide and one for sitagliptin; none were severe or nocturnal. Conclusions: Liraglutide provided better glycaemic control and greater body weight reduction than sitagliptin when administered as add‐on to metformin. More patients had nausea, diarrhoea and decreased appetite with liraglutide versus sitagliptin.